Morocco : Second Review Under the Arrangement Under the Precautionary and Liquidity Line-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Morocco's Second Review Under the Arrangement Under the Precautionary and Liquidity Line. The authorities are committed to further reduce fiscal and external vulnerabilities, while strengthening the foundations for higher and more inclusive growth. Building on recent progress in improving the business environment, sustained reforms are needed to raise potential growth and reduce high unemployment, especially among the youth, increase female labor participation, and reduce regional disparities. Reforms of education, governance, and the labor market should contribute to more private sector-led growth and job creation. Considering the slowdown in fiscal consolidation, stepped up tax reforms and contained wage bill are needed to lower the public debt-to-gross domestic product ratio while securing priority investment and social spending in the medium term. A decisive and comprehensive tax reform should aim to secure adequate revenues while bringing about greater equity and simplicity of the tax system. The transition to greater exchange rate flexibility initiated in 2018 would enhance the economy's capacity to absorb shocks and preserve its external competitiveness.